Genomic Sequence and Transcriptome Analysis of the Medicinal Fungus Keithomyces neogunnii. (24th February 2022) - Long, Liangkun; Liu, Zhen; Deng, Chunying; Li, Chuanhua; Wu, Liangliang; Hou, Beiwei; Lin, Qunying
Abstract: The filamentous fungus Keithomyces neogunnii can infect the larvae of Lepidoptera ( Hepialus sp.) and form an insect–fungi complex, which is utilized as an important traditional Chinese medicine. As a valuable medicinal fungus, K. neogunnii produces diverse bioactive substances (e.g., polysaccharide, vitamins, cordycepic acid, and adenosine) under cultivation conditions. Herein, we report the first high-quality genome of the K. neogunnii single-spore isolate Cg7.2a using single-molecule real-time sequencing technology in combination with Illumina sequencing. The assembled genome was 32.6 Mb in size, containing 8, 641 predicted genes and having a GC content of 52.16%. RNA sequencing analysis revealed the maximum number of differentially expressed genes in the fungus during the stroma formation stage compared with those during the mycelium stage. These data are valuable to enhance our understanding of the biology, development, evolution, and physiological metabolism of K. neogunnii .